ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PENYEWA DALAM UPAYA MENINGKATKAN LOYALITAS PENYEWA (Studi kasus: PT. GRAND INDONESIA) - Shelfy Indah R (Universitas Mercu Buana, 2014)
Abstract: The research aims are to analyze influance of Serve Quality toward to Costumer Satisfaction in effort to increase Customer Loyalty. Data was collected through questioner and it was implemented to PT Grand Indonesia Shopping Mall 100 stores at PT Grand Indonesia Shopping Mall. This research sampling technique used explanatory research method and used validity test by product moment and alfa cronbach reliability test. This research also used Path Analysis to verify and to prove research analysis. Analysis result demonstrate that Service Quality has positive significant toward to Customer Satisfaction and increase Customer Loyalty PT Grand Indonesia Shopping Mall.Keywords: Service Quality, Customer Satisfactions, Customer Loyalty